2020
DOI: 10.1590/1678-9199-jvatitd-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory lesions and brain tumors: is it possible to differentiate them based on texture features in magnetic resonance imaging?

Abstract: Background: Neuroimaging strategies are essential to locate, to elucidate the etiology, and to the follow up of brain disease patients. Magnetic resonance imaging (MRI) provides good cerebral soft-tissue contrast detection and diagnostic sensitivity. Inflammatory lesions and tumors are common brain diseases that may present a similar pattern of a cerebral ring enhancing lesion on MRI, and non-enhancing core (which may reflect cystic components or necrosis) leading to misdiagnosis. Texture analysis (TA) and mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Inflammatory brain lesions and tumors may have a similar pattern of ring enhancement around a non-enhancing core of cystic components or necrosis. 8 Glioblastoma tends to be more spherical than brain abscess, which can help differentiating these conditions. 9 Texture analysis of ring-enhancing lesions on MRI based on machine learning approaches are computer-aided diagnostic tools that can assist radiologists in differentiating inflammatory brain lesions from tumors.…”
Section: Questions/discussion Points Partmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory brain lesions and tumors may have a similar pattern of ring enhancement around a non-enhancing core of cystic components or necrosis. 8 Glioblastoma tends to be more spherical than brain abscess, which can help differentiating these conditions. 9 Texture analysis of ring-enhancing lesions on MRI based on machine learning approaches are computer-aided diagnostic tools that can assist radiologists in differentiating inflammatory brain lesions from tumors.…”
Section: Questions/discussion Points Partmentioning
confidence: 99%
“… 9 Texture analysis of ring-enhancing lesions on MRI based on machine learning approaches are computer-aided diagnostic tools that can assist radiologists in differentiating inflammatory brain lesions from tumors. 8 …”
Section: Questions/discussion Points Partmentioning
confidence: 99%
“…Furthermore, these tissues often have indistinguishable intensity features in structural MRI sequences, such as T1-w, T2-w, FLAIR. For instance, the difficulty in differentiating between the core tumor and associated inflammation was discussed [ 19 ]. In addition to that, Alves et al [ 19 ] demonstrated the difficulty in differentiating tumors using signal intensities alone.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the difficulty in differentiating between the core tumor and associated inflammation was discussed [ 19 ]. In addition to that, Alves et al [ 19 ] demonstrated the difficulty in differentiating tumors using signal intensities alone. They demonstrated using a case where two patients were diagnosed with two different brain tumor types due to both tumors have similar intensity features and both are surrounded by extensive edema.…”
Section: Introductionmentioning
confidence: 99%
“…The features used during texture analysis are mathematical parameters calculated from the distribution of pixels, which characterize the texture type in the image. The main image processing disciplines in which texture analysis techniques are used are classification, segmentation, and synthesis of dissimilar features including normal tissue, inflammatory regions and tumors ( Pietikäinen et al, 2000 , Alves et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%